DETERMINAN KEPATUHAN PROTOKOL KESEHATAN COVID-19 DI KELURAHAN 20 ILIR D-II KEMUNING PALEMBANG - Rahmalia Afriyani; Apriani Apriani; Ramadhani Firmansyah; Anur Rohmin; Asih Fatriansari; Retalia Ayu (JURNAL KESEHATAN INDRA HUSADA, 2022)
The spread of the Covid-19 chain can be controlled by complying with health protocols. The purpose of this study was to determine the factors that influence community compliance with the COVID-19 health protocol in Kelurahan 20 ilir D II Kemuning Palembang in 2021. This study used a cross sectional approach conducted on 29 May to 31 June 2021. The sample in this study was People in RT. 34 RW. 004 Kelurahan 20 Ilir D.II Kemuning totaling 100 respondents. The results of the study found that there was a significant relationship between health protocol compliance with factors of knowledge (p 0.002), motivation (p 0.019), education (0.009), and age (0.043). On the other hand, there is no significant relationship between gender and compliance with the Covid-19 health protocol (0.153). The most dominant factor influencing compliance with the Covid-19 health protocol is knowledge with an OR of 4.225. Health education about health protocols is important to increase public knowledge.